Best Answer

Assuming your quesiton is Multiply x times 3x times 4, the answer would be 3x squared times 4.

Lvl 1

12

Q: Multiply x 3x 4

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

3x * (x - 4) = 3x*x - 3x*4 = 3x^2 - 12x.

For any x ≠ 0, x2 -10/x2 - 4 +3x/x2 - 4 LCD = x2, multiply each term by their missing element of LCD = (x4 + 10 +3x - 8x2)/x = (x4 - 8x2 + 3x + 10)/x2

Since you cannot multiply x by a, in the answer you get ax. 2a * 3x = 6ax

(x/4) - 4 = (3x/4) - 6 The first step to solving this equation is to multiply the entire equation by 4 to eliminate the denominators under x. Doing so yields the equation: x - 16 = 3x - 24 Simply combining like-terms will yield 2x = 8 So x is equal to 4

3x-1=11 (3x-1)+1=11+1 3x=12 (3x)x(1/3)=12 x (1/3) x=4 x^2+4 16+4 =20

Related questions

it means you multiply the number or variable by it self three times.For example,43 = 4*4*4 = 6453 = 5*5*5 = 125x3 = x*x*x3x3 = 3*x*x*x(3x)3 = 3x*3x*3x= 27x3

Find two numbers differing by 3 which multiply to 28. 4 and 7 will do. (x + 7)(x - 4)

Multiply out the factors and then you can check: (x + 2)(x + 3) = x² + 3x + 2x + 6 = x² + 5x + 6 ≠ x² + 3x + 4 Therefore False.

3x * (x - 4) = 3x*x - 3x*4 = 3x^2 - 12x.

It depends. If you meant 8x-4=3x+1 then: 5x=5 x=1 But if you meant 8(x-4)=3(x+1) then: 8x-32=3x+3 5x=35 x=7

3x * (x - 4) = 3x*x - 3x*4 = 3x^2 - 12x.

For any x ≠ 0, x2 -10/x2 - 4 +3x/x2 - 4 LCD = x2, multiply each term by their missing element of LCD = (x4 + 10 +3x - 8x2)/x = (x4 - 8x2 + 3x + 10)/x2

Since you cannot multiply x by a, in the answer you get ax. 2a * 3x = 6ax

You simply multiply the expression on the outside (in this case, 3) by each of the expressions inside the parentheses, and add everything up. In this case, 3x + 3 times 4.

3x/(5-x)/3=4 3x/(5-x)=4X3 3x=12(5-x) 3x=60-12x 3x+12x=60 x=4

(x2+3x-4) (x-4)

If that's -3x, the answer is (x - 7)(x + 4) If that's +3x, the answer is (x + 7)(x - 4)